2017
DOI: 10.1039/c7ra03727a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles co-delivering pVSVMP and pIL12 for synergistic gene therapy of colon cancer

Abstract: Nanoparticles delivering therapeutic genes have promising applications in cancer treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In another work, the Gou group developed heparin-polyethyleneimine (HPEI) nanoparticles to codeliver two plasmids encoding vesicular stomatitis virus matrix protein (VSVMP) and IL-12 (namely, HPEI/pIL12+pVSVMP), and confirmed that the nanoparticles could effectively deliver genes and enhance the effect of gene therapy (Figure 3A). 141 The obtained HPEI/pIL12+pVSVMP complexes not only promoted the apoptosis of C-26 cells in vitro but also significantly inhibited the proliferation of tumor cells as shown by K i67 staining results (Figure 3B and C). Moreover, the complexes resulted in T lymphocytes activation on a C-26 colon cancer model, thereby greatly reducing tumor metastasis nodules number and promoting anticancer immunity (Figure 3D).…”
Section: Delivery Of Immunomodulators With Nanomaterialsmentioning
confidence: 72%
See 2 more Smart Citations
“…In another work, the Gou group developed heparin-polyethyleneimine (HPEI) nanoparticles to codeliver two plasmids encoding vesicular stomatitis virus matrix protein (VSVMP) and IL-12 (namely, HPEI/pIL12+pVSVMP), and confirmed that the nanoparticles could effectively deliver genes and enhance the effect of gene therapy (Figure 3A). 141 The obtained HPEI/pIL12+pVSVMP complexes not only promoted the apoptosis of C-26 cells in vitro but also significantly inhibited the proliferation of tumor cells as shown by K i67 staining results (Figure 3B and C). Moreover, the complexes resulted in T lymphocytes activation on a C-26 colon cancer model, thereby greatly reducing tumor metastasis nodules number and promoting anticancer immunity (Figure 3D).…”
Section: Delivery Of Immunomodulators With Nanomaterialsmentioning
confidence: 72%
“…Because of the strong protective effect of nanoparticles on plasmids, DTPA-modified PEI nanoparticles significantly increased IL-12 levels on the HepG2 cell line compared to unmodified PEI. In another work, the Gou group developed heparin-polyethyleneimine (HPEI) nanoparticles to codeliver two plasmids encoding vesicular stomatitis virus matrix protein (VSVMP) and IL-12 (namely, HPEI/pIL12+pVSVMP), and confirmed that the nanoparticles could effectively deliver genes and enhance the effect of gene therapy (Figure A) . The obtained HPEI/pIL12+pVSVMP complexes not only promoted the apoptosis of C-26 cells in vitro but also significantly inhibited the proliferation of tumor cells as shown by K i 67 staining results (Figure B and C).…”
Section: Delivery Of Immunomodulators With Nanomaterialsmentioning
confidence: 80%
See 1 more Smart Citation
“…IL-12 could activate both innate NK and CD8 + T cells for induction of tumor cell apoptosis, which together potentiated VSVMP-mediated anti-tumor effects and restrained the colonization of DTCs. 159 During the establishment of metastasis niches, DTCs actively recruit inflammatory cells (such as macrophages and monocytes), furthermore facilitating the extravasation of DTCs and the formation of immunosuppressive TME. Consequently, these immune cells are potential targets for tumor metastasis management.…”
Section: Tumor Immune Equilibrium: Nanoparticle-based Immunotherapy F...mentioning
confidence: 99%
“…However, the treatment for soft tissue injury is still a big challenge in clinical practise as the curative effects of the above methods are not satisfactory [ 2 , 5 ]. Synergistic therapy is a widely explored method to improved curative effects for cancer therapy [ 6 , 7 ], which possesses improved curative effects compared with the cures using single drug or way. However, this method has been rarely explored in the treatment of injured soft tissues.…”
Section: Introductionmentioning
confidence: 99%